2020
DOI: 10.1097/rhu.0000000000001594
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Deaminase Gene Polymorphism and Baseline Serum Level of Adenosine Deaminase as a Biomarker of Response to Methotrexate in Rheumatoid Arthritis

Abstract: BackgroundMethotrexate (MTX) is the first-line therapy for rheumatoid arthritis (RA), but nearly 30% of RA patients do not respond to it. Methotrexate acts by enhancing the level of adenosine, which gets converted to inosine by the enzyme adenosine deaminase (ADA). We studied whether ADA gene polymorphism and serum levels of total ADA are associated with responsiveness to MTX.MethodsTwo hundred seven disease-modifying antirheumatic drug–naive active RA patients (DAS28-ESR [Disease Activity Score–28 for rheumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Previous studies have suggested correlation between ADA activity and RA joint inflammation (Gao et al 2020 ; Nair et al 2020 ; Gangadharan et al 2021 ). The results demonstrated that there was significant increase in ankle joint ADA activity and mRNA levels in RA rats compared with control rats.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have suggested correlation between ADA activity and RA joint inflammation (Gao et al 2020 ; Nair et al 2020 ; Gangadharan et al 2021 ). The results demonstrated that there was significant increase in ankle joint ADA activity and mRNA levels in RA rats compared with control rats.…”
Section: Discussionmentioning
confidence: 95%
“…As a result, detecting low CD39 mean fluorescence intensity (MFI) on Tregs using FACS on a small sample of whole peripheral blood represents a noninvasive, rapid, and convenient procedure for predicting MTX nonresponsiveness in RA patients with >99 percent confidence, and thus represents a valuable option for RA therapy ( 16 ). On the other hand, studies on the ADO deaminase gene polymorphism and baseline serum level of ADO deaminase have shown that they do not correlate with MTX response ( 17 ).…”
Section: Potential Biomarkers For the Response To Methotrexate Therapymentioning
confidence: 99%